EFL Learners’ Attitudes towards the Use of Communicative Activities to Improve Spoken Communicative Competence - Lembarek , Dr. Samira Sayah (Migration Letters, 2024)
The present paper aims to investigate the learners’ attitudes towards using speaking activities in the classroom to promote their spoken communicative competence. More importantly, it sheds light on the effectiveness of communicative activities in enhancing the learners’ communicative abilities. A quantitative approach is adopted, and a questionnaire is administered to thirty third-year English students at the University of Ouargla. The results revealed that most students are interested in developing their oral capacities through structured communicative activities. However, the flow of speaking cannot be devoid of obstacles that may lead to learners’ passivity (e.g., shyness, lack of motivation, lack of confidence, lack of linguistic competence, and so on). As a remedy, EFL learners can overcome their reluctance and improve their oral capacities by creating group discussions outside the classroom where they have opportunities to participate in real-life communicative contexts.